The Effect Of Segmentation And Targeting In Increasing Sales Of Nu Salt Brand Consumption (Case Study In The Market Of Muslimat Religious Organizations Wil. Central Java) - Dias Eko Erry Akhmadi; Damajanti Sri Lestari; Anita Asnawi; Moh. Arfani (International Journal of Economics, Business and Innovation Research, 2025)
This study specifically investigates how segmentation and targeting strategies, which are often considered conventional steps in marketing, actually show unusual dynamics in encouraging an increase in sales of NU Salt brand consumption salt products, especially in the market of NU Muslimat religious organizations in the Central Java region. NU Salt products are produced by the Sari Makmur Rembang Farmers Cooperative, which is one of the national salt production centers. The marketing approach through the NU Muslimat community was chosen because of the characteristics of a loyal market, homogeneous in values, and having an organizational structure that allows for more targeted market penetration. This study adopts a quantitative approach through a survey method, with the collection of primary data directly from a total of 96 respondents who are NU Muslimat members who are NU Salt consumers. The data analysis technique applied was multiple linear regression using the help of SPSS software, to test the relationship between segmentation (X1) and targeting (X2) variables to increase sales (Y). The results of the study showed that both segmentation and targeting had a positive and significant effect on the increase in sales, both partially and simultaneouslyThe results of the F test indicated that both variables simultaneously had a significant influence on the increase in sales with a significant value of 0.000. The t-test showed that the variables X1 and X2 also had a significant influence separately. The Adjusted R Square value of 0.611 indicates that 61.1% of the variation in sales increase can be explained by segmentation and targeting strategies, although this fairly high proportion appears in the context of low-differentiated commodity products, which in theory rarely show such a strong correlation. These findings make a practical contribution to developing community-based marketing strategies, especially for religious organizations, and at the same time affirm the importance of a deep understanding of market characteristics in improving the sales performance of local products.